Effects of Chilling and Partial Freezing on Rigor Mortis Changes of Bighead Carp (Aristichthys nobilis) Fillets: Cathepsin Activity, Protein Degradation and Microstructure of Myofibrils. Issue 12 (10th November 2015) - Lu, Han; Liu, Xiaochang; Zhang, Yuemei; Wang, Hang; Luo, Yongkang
Abstract: To investigate the effects of chilling and partial freezing on rigor mortis changes in bighead carp ( Aristichthys nobilis ), pH, cathepsin B, cathepsin B+L activities, SDS‐PAGE of sarcoplasmic and myofibrillar proteins, texture, and changes in microstructure of fillets at 4 °C and –3 °C were determined at 0, 2, 4, 8, 12, 24, 48, and 72 h after slaughter. The results indicated that pH of fillets (6.50 to 6.80) was appropriate for cathepsin function during the rigor mortis . For fillets that were chilled and partially frozen, the cathepsin activity in lysosome increased consistently during the first 12 h, followed by a decrease from the 12 to 24 h, which paralleled an increase in activity in heavy mitochondria, myofibrils and sarcoplasm. There was no significant difference in cathepsin activity in lysosomes between fillets at 4 °C and –3 °C ( P > 0.05). Partially frozen fillets had greater cathepsin activity in heavy mitochondria than chilled samples from the 48 to 72 h. In addition, partially frozen fillets showed higher cathepsin activity in sarcoplasm and lower cathepsin activity in myofibrils compared with chilled fillets. Correspondingly, we observed degradation of α‐actinin (105 kDa) by cathepsin L in chilled fillets and degradation of creatine kinase (41 kDa) by cathepsin B in partially frozen fillets during the rigor mortis . The decline of hardness for both fillets might be attributed to the accumulation of cathepsin in myofibrils from the 8 to 24 h. The lower cathepsin activity in myofibrils for fillets that were partially frozen might induce a more intact cytoskeletal structure than fillets that were chilled.